Influence of the sport specific training background on the symmetry of the single legged vertical counter movement jump among female ballet dancers and volleyball players - V. Bartol; R. Vauhnik; D. Rugelj (Heliyon, 2022)
Introduction: Vertical jumps are the key components of performance in the classical ballet and volleyball. Asymmetry of performance between the lower extremities is a potential risk factor for injury. Purpose: The purpose of this study was to analyse the symmetry of the unilateral vertical countermovement jump (CMJ) in a group of female ballet dancers and in a group of female college volleyball players. Methods: We tested the CMJ with the dominant and nondominant leg and the bilateral CMJ among 15 female ballet dancers and 15 female volleyball players aged 18–24 years. Ground reaction forces were recorded with the force plate and five variables were analysed - jump height, power, energy, and time to flight and time to maximum force during landing. Results: 2 × 2 repeated measures of ANOVA indicates that type of sport is influencing some of the single leg CMJ variables (energy used and time to maximal force in landing), there was a significant asymmetry between dominant and non-dominant leg in some of the vertical CMJ variables (CMJ height, energy used and the average power was marginally significant). The interaction between the type of sport and leg dominance however was not significant for all of the analysed CMJ variables indicating no difference in asymmetry between the dominant and non-dominant leg in the two investigated sports. The results expressed in the percentage differences between both legs that is widely used in the scientific literature showed that ballet dancers exhibited more symmetrical CMJ height, power, and energy compared to volleyball players. The average percent difference in CMJ height between the dominant and non-dominant leg was 4.26 (10.60) % and 13.36 (14.72) %, respectively. On average, volleyball players jumped slightly higher at the bilateral CMJ (p < 0.001). Conclusion: Sport-specific training background could explain the observed contralateral deficit differences between two sport groups. The elements of ballet training could be introduced into the volleyball training to overcome observed this contralateral deficit.